2000
DOI: 10.1007/s11745-000-0570-6
|View full text |Cite
|
Sign up to set email alerts
|

Lipid metabolism and tissue composition in Atlantic salmon (Salmo salar L.)—Effects of capelin oil, palm oil, and oleic acid‐enriched sunflower oil as dietary lipid sources

Abstract: Triplicate groups of Atlantic salmon (Salmo salar L.) were fed four diets containing different oils as the sole lipid source, i.e., capelin oil, oleic acid-enriched sunflower oil, a 1:1 (w/w) mixture of capelin oil and oleic acid-enriched sunflower oil, and palm oil (PO). The beta-oxidation capacity, protein utilization, digestibility of dietary fatty acids and fatty acid composition of lipoproteins, plasma, liver, belly flap, red and white muscle were measured. Further, the lipid class and protein levels in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

49
287
1
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 330 publications
(340 citation statements)
references
References 42 publications
49
287
1
3
Order By: Relevance
“…The assay of fatty acid oxidation in intact hepatocytes requires the determination of acidsoluble radioactivity as described in detail previously Torstensen et al 2000). Briefly, the 1 ml of cell suspension was homogenized and centrifuged at 2000 g for 10 min in a microcentrifuge.…”
Section: Assay Of Hepatocyte and Enterocyte Fatty Acyl Oxidation Actimentioning
confidence: 99%
See 1 more Smart Citation
“…The assay of fatty acid oxidation in intact hepatocytes requires the determination of acidsoluble radioactivity as described in detail previously Torstensen et al 2000). Briefly, the 1 ml of cell suspension was homogenized and centrifuged at 2000 g for 10 min in a microcentrifuge.…”
Section: Assay Of Hepatocyte and Enterocyte Fatty Acyl Oxidation Actimentioning
confidence: 99%
“…Vegetable oils such as rapeseed, linseed and olive are potential candidates to partially replace fish oil, and blends of these oils could also be an alternative in marine aquaculture diets. It is also of interest to investigate palm oil as a dietary oil source for marine fish as palm oil production is predicted to exceed soybean oil production within the next 10 years making it the most abundant vegetable oil in the world (Gunstone, 2001), and it has been used successfully in diets for salmonid species (Torstensen et al, 2000;Bell et al, 2002). Therefore, there is currently great interest in the regulation of HUFA biosynthesis in fish to determine the effectiveness with which vegetable oils can be utilized to replace FO in the diets of commercially important cultured fish species .…”
Section: Introductionmentioning
confidence: 99%
“…However, the finite and limited supply of these marine ingredients, as well as the continued increase in aquaculture production, has resulted in a research for alternative raw materials for aquafeeds (11)(12)(13)(14) . In this context, considerable research has focused on sustainable alternatives such as terrestrial plant sources (15,16) , which have been demonstrated to be suitable for Atlantic salmon (Salmo salar L.) growth (11,(17)(18)(19)(20) . A considerable body of literature exists regarding the effect of FM/FO substitution on the n-3 LC-PUFA content of fish, although limited attention has so far been focused on the effect of this substitution on other beneficial nutrients such as Se.…”
mentioning
confidence: 99%
“…Linseed oil (LO) is among the most common vegetable oils examined, singly or in combination, in researches for fish feed production including gilthead seabream (reviewed by Nasopoulou and Zebatakis, 2012), whereas sunflower oil (SFO) was not previously evaluated for the species. However, reports on using sunflower oil in feeds for Atlantic salmon (Salmo salar) (Torestensen et al, 2000;Bransden et al, 2003;Menoyo et al, 2007) and European seabass (Dicentrarchus labrax) (Yieldiz and Sener, 2004) are promising. In the present study, first report, incremental levels of either SFO or LO (40-56 g kg −1 diet) were individually evaluated as partial substitutes to fish oil in gilthead seabream fingerling feeds.…”
Section: Discussionmentioning
confidence: 99%
“…Despite, LO have already been studied, either singly or mixed, within highly energetic (25% L) fish meal (FM)-based diets (Izquierdo et al, 2003) or plant-protein rich diets (Benedito-Palos et al, 2008) for gilthead seabream, the high level of n-3 LNA makes this oil relatively unique in being able provide dietary n-3 PUFA at a potentially cost effective rate. On the other hand, reports on using sunflower oil (SFO) as a possible substantial partial substitute for dietary fish oil were mostly limited to Atlantic salmon, Salmo salar (Bell et al, 1993;Bransden et al, 2003;Menoyo et al, 2007;Torestensen et al, 2000), and European seabass, Dicentrarchus labrax (Yildiz and Sener, 2004). Moreover, the high levels of dietary fish oil substitution up to 80% or 100% in gilthead seabream feeds had evidenced to result in a remarkably reduced growth performance and feed utilization efficiency and increased feed conversion ratio as well as liver weight and lipid content (Glencross, 2009;Izquierdo et al, 2005;Menoyo et al, 2004;Nasopoulou and Zabetakis, 2012).…”
Section: Introductionmentioning
confidence: 99%